A Disequilibrium Macroeconomic Model: The Implications of a Correction - Korliras, Panayotis G. (Quarterly Journal of Economics, 1980)
Journal Article A Disequilibrium Macroeconomic Model: The Implications of a Correction Get access Panayotis G. Korliras Panayotis G. Korliras Athens School of Economics and Business Science Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 95, Issue 1, August 1980, Pages 199–200, https://doi.org/10.2307/1885358 Published: 01 August 1980